Reduced Orbitofrontal Gray Matter Concentration as a Marker of Premorbid Childhood Trauma in Cocaine Use Disorder - Bachi, Keren; Parvaz, Muhammad A.; Moeller, Scott J.; Gan, Gabriela; Zilverstand, Anna; Goldstein, Rita Z.; Alia-Klein, Nelly (Frontiers in Human Neuroscience, 2018)
Background Childhood trauma affects neurodevelopment and promotes vulnerability to impaired constraint, depression, and addiction. Reduced gray matter concentration (GMC) in the mesocorticolimbic regions implicated in reward processing and cognitive control may be an underlying substrate, as documented separately in addiction and for childhood trauma. The purpose of this study was to understand the contribution of childhood maltreatment to GMC effects in individuals with cocaine use disorder. Methods Individuals with cocaine use disorder were partitioned into groups of low versus high childhood trauma based on median split of the total score of the Childhood Trauma Questionnaire (CUD-L, N=23; CUD-H, N=24) and compared with age, race, and gender matched healthy controls with low trauma (N=29). GMC was obtained using voxel-based morphometry applied to T1-weighted MRI scans. Drug use, depression and constraint were assessed with standardized instruments. Results Whole-brain group comparisons showed reduced GMC in the right lateral orbitofrontal cortex (OFC) in CUD-H as compared with controls (cluster-level pFWE-corr <.001) and CUD-L (cluster-level pFWE-corr =.035); there were no significant differences between CUD-L and controls. A hierarchical regression analysis across both CUD groups revealed that childhood trauma, but not demographics and drug use, and beyond constraint and depression, accounted for 37.7% of the variance in the GMC in the right lateral OFC (p<.001). Conclusions Beyond other contributing factors, childhood trauma predicted GMC reductions in the OFC in individuals with cocaine use disorder. These findings underscore a link between premorbid environmental stress and morphological integrity of a brain region central for behaviors underlying drug addiction. These results further highlight the importance of accounting for childhood trauma, potentially as a factor predisposing to addiction, when examining and interpreting neural alterations in cocaine addicted individuals.